Maritime Piracy in Nigeria: A Survey-Based Study of Root Causes, Security Challenges and Policy Responses - Olumuyiwa Olutosin Ajayi; Joy Obiageli Iyamah; Ugochukwu David Abasilim (PERSPEKTIF, 2025)
Maritime piracy is a significant concern for Nigeria's economy, local development, and national security, particularly in Bayelsa State, which is a key port site in the Gulf of Guinea. The national and international efforts of all parties involved have not led to an improvement in the situation, and maritime piracy continues to threaten economic opportunities, national security, and the livelihoods of individuals. This study examined the deeper and proximate sources of maritime piracy in Bayelsa, focusing on the legal and policy responses required for effective policymaking. Using a cross-sectional survey design and a mixed-methods approach, data were collected from 300 respondents across the Brass, Otuoke, Nembe, and Ogbia Local Government Areas, employing cluster sampling methods. The quantitative data were descriptively analyzed using SPSS Version 25, and ANOVA and Spearman's Rank Correlation tests were used to test the hypotheses. The results established the links between maritime insecurity and youth unemployment, environmental degradation, poverty, and weak institutional governance. The research utilizes Relative Deprivation Theory (RDT) to demonstrate how feelings of inequality can foster resentment, and it employs Frustration–Aggression Theory (FAT) to illustrate how frustrated aspirations may lead to aggression and violence, especially the clear relationship between feelings of marginalization and piracy. Additionally, the study backs the shift away from militaristic, reactionary solutions to inclusive, preventative, and developmental responses to global piracy in the region.  Ultimately, achieving enduring peace in the Bayelsa maritime corridor requires a multi-stakeholder strategy that incorporates human security as a key ethical consideration in the formulation and implementation of policies.